Antibiofilm and antivirulence properties of chitosan-polypyrrole nanocomposites to Pseudomonas aeruginosa. (March 2019) - Khan, Fazlurrahman; Manivasagan, Panchanathan; Pham, Dung Thuy Nguyen; Oh, Junghwan; Kim, Shin-Kwon; Kim, Young-Mog
Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen which exhibits its property of pathogenesis due to several factors, including the formation of biofilm and production of several virulence factors. Development of resistance properties against antibiotics leads to the discovery of certain alternative strategies to combat its pathogenesis. In the present study, a highly stable, biocompatible and water soluble nanocomposites (NCs) are synthesized from chitosan (CS) and the polypyrrole (PPy). The resultant chitosan-polypyrrole nanocomposites (CS-PPy NCs) inhibit the establishment of biofilm and also eradicate the preformed matured biofilm formed by P. aeruginosa . CS-PPy NCs inhibit the hemolytic and protease activities of P. aeruginosa . The NCs significantly reduce the production of many virulence factors such as pyocyanin, pyroverdine and rhamnolipid. CS-PPy NCs also suppress the bacterial motility such as swimming and swarming. The present study showed that highly stable CS-PPy NCs act as a potent antibiofilm and antivirulence drug for the treatment of P. aeruginosa infection. Graphical abstract: Image 1 Highlights: CS-PPy is a water soluble and highly stable nanocomposites. CS-PPy NCs inhibits the formation of biofilm of P. aeruginosa. CS-PPy NCs exhibits antihemolytic and antivirulence properties to P. aeruginosa. CS-PPy NCs impairs the motilities properties of P. aeruginosa. CS-PPy NCs can be used as a potent antibiofilm and antivirulence drug.